ANALISIS PEMBELAJARAN IPA TERPADU DITINJAU DARI KEMAMPUAN SCIENCE INQUIRY SISWA KELAS VIII SMP PGRI 01 SEMARANG - Aili liila; Joko Siswanto; Fenny Roshayanti (JURNAL ILMIAH EDUKATIF, 2021)
Natural science or science is the study of natural phenomena which includes living and non-living creatures or related to life and the physical world. Meanwhile the government has arranged in Permendiknas No. 20 of 2006, that learning science in junior high school should be given in an integrated manner. Through integrated science learning students can gain direct experience, so they can add strength to receive, save, and apply the concepts they have learned. Scientific inquiry learning is designed to get students involved in an investigation, emphasizing the activeness of students in finding their own core of learning material, while the teacher trains and gives students freedom of thought. This paper was conducted with a qualitative research with a descriptive approach in which the data were obtained from interviews and observations with teachers who teach in class VIII SMP PGRI 01 Semarang this study was conducted in depth.